A primer binder and a preparation method thereof, an electrode sheet, and an electrochemical device

CN122889760APending Publication Date: 2026-10-09JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147927.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]针对正极集流体的底涂层技术中存在的界面结合力弱、缺乏主动设计的锚点结构、与粘结剂体系适配性差等技术问题,本发明的目的在于提供一种底涂集流体及其制备方法、极片和电化学装置

Benefits of technology

本发明首创了球形颗粒锚点与导电体系协同作用的涂层设计,克服了集流体金属表面与活性物质层界面结合力不足的缺陷,通过引入两种粒径范围的球形颗粒搭配特定的导电材料在集流体表面构建表面均匀分布有多级凹凸锚点结构功能涂层,有效提升后续涂覆的活性物质层的粘结剂体系与功能涂层间的界面结合强度,从而有效提升活性物质层与集流体之间的界面剥离强度。同时,本发明采用碳纳米管在凹凸锚点之间长程搭接,形成连续导电桥,该结构通过穿插和搭接的方式在涂层中形成连续的导电通路,有效改善集流体与活性层之间的界面接触阻抗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of bottom coating current collector and preparation method thereof, pole piece and electrochemical device.The bottom coating current collector includes current collector and the functional coating of at least one surface of the current collector, the functional coating includes binder, conductive material and spherical particle;The spherical particle at least part protrudes from the surface of the functional coating for forming concave-convex structure, and the conductive material is bridged between spherical particle, and continuous electron transport path is constructed.The application constructs concave-convex anchor point structure on the surface of bottom coating current collector, forms mechanical occlusion between binder, significantly improves and active interface peeling strength;Carbon black filling is matched with carbon nanotube long-range lapping, and three-dimensional conductive network is constructed, interface contact resistance is reduced, and electrode polarization is relieved;Spherical particle acts as skeleton buffer volume stress, inhibits coating cracking, and prolongs battery cycle life.The present scheme adapts existing positive electrode mass production process, and additional production cost is low, with scale application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a base-coated current collector and its preparation method, an electrode, and an electrochemical device. Background Technology

[0002] In the field of lithium-ion battery manufacturing, electrodes typically use traditional metal foil or composite metal foil as current collectors, and the active material layer is coated onto the metal foil surface using polyvinylidene fluoride (PVDF) binder. However, as battery technology continues to develop towards higher energy density and faster charging rates, the coating surface density and rolling compaction density of the electrodes are constantly increasing, placing more stringent requirements on the stability of the electrode structure and long-term cycle reliability. Against this backdrop, the problem of weak interfacial bonding between the smooth metal foil surface and the PVDF bonding system due to the scarcity of effective anchoring points is becoming increasingly prominent. The metal foil surface is usually relatively flat and smooth, and the PVDF binder mainly relies on limited van der Waals forces to bond with it, lacking an effective mechanical interlocking or locking structure. Under conditions of repeated volume expansion of the active material during electrode rolling, battery assembly bending, and long-term charge and discharge processes, delamination or powder shedding between the active material layer and the current collector is highly likely to occur. Even when aluminum foil is pretreated with a single conductive carbon black coating, the resulting coating structure is often dense and the surface remains relatively smooth. This makes it difficult to provide sufficient physical anchoring points for the upper-coated cathode slurry, resulting in low interfacial peel strength, which fails to meet the stringent requirements of high-load electrodes. Especially for high areal density cathodes, microcracks will emerge and gradually expand within the active material during long cycles. If the interfacial adhesion is insufficient, these microcracks can easily induce interfacial debonding, causing the internal contact resistance of the battery to continuously increase and the capacity retention rate to rapidly decline, severely restricting the cycle life and reliability of the battery.

[0003] To address the aforementioned issues, existing technical improvements mostly focus on optimizing PVDF binder formulations or adding tackifiers, with extremely limited effectiveness. Therefore, they fail to fundamentally solve the industry-wide problem of insufficient interfacial bonding between the active material and the current collector. Consequently, the industry urgently needs to develop a novel functional coating system for application to the current collector surface. By constructing a functionalized coating structure with multi-level anchor points on the current collector surface, the bonding strength and long-term operational stability between the active material layer and the current collector can be significantly improved without altering existing electrode fabrication processes.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] To address the technical problems existing in the undercoating technology of positive electrode current collectors, such as weak interfacial bonding, lack of actively designed anchor point structure, and poor compatibility with binder system, the present invention aims to provide an undercoating current collector, its preparation method, electrode, and electrochemical device.

[0006] This invention is implemented as follows: In a first aspect, the present invention provides a current collector with a micro-anchor structure, wherein the primer current collector includes a current collector and a functional coating disposed on at least one surface of the current collector; the functional coating includes spherical particles in a mass ratio of 1:(0.5-4):(1-6), a conductive material, and a binder; The conductive material includes carbon nanotubes; in the spherical particles, the ratio of the particle size D501 of the first spherical particle to the particle size D502 of the second spherical particle is 1:(1.5-4); the spherical particles at least partially protrude from the surface of the functional coating to form an uneven structure, and the carbon nanotubes bridge the spherical particles to form a continuous electron transport pathway.

[0007] In an optional embodiment, the conductive material further includes carbon black, wherein the mass ratio of carbon black to carbon nanotubes is 1:(2-25). And / or, the mass ratio of the first spherical particle to the second spherical particle is 1:(0.5-2); And / or, the length L of the carbon nanotube satisfies the following relationship with the particle size D501 of the first spherical particle and the particle size D502 of the second spherical particle: 2D501≤L≤6D502; And / or, the particle size D503 of the carbon black is 20nm-40nm.

[0008] In an optional embodiment, the diameter of the carbon nanotubes is 10 nm-20 nm; And / or, the spherical particles comprise at least one of silica, alumina, or polymethyl methacrylate polymer; And / or, the sphericity of the spherical particles is not less than 95%; And / or, the adhesive is at least one of polyvinylidene fluoride, polyacrylic acid resin or styrene-butadiene rubber; And / or, the current collector is selected from at least one of aluminum foil, copper foil, composite aluminum foil, and composite copper foil.

[0009] In an optional embodiment, the particle size D501 of the first spherical particle is 0.5μm-1μm, and the particle size D502 of the second spherical particle is 1.5μm-2.0μm. And / or, the thickness of the functional coating is 0.8μm-2μm; And / or, the spherical particles are fluorine-modified spherical particles.

[0010] In an optional embodiment, the raw materials for preparing the functional coating, by 100% by mass, include: 4%-8% binder, 2%-6% conductive material, 1.5%-4.0% spherical particles, and the balance being solvent. The solvent is selected from at least one of N-methylpyrrolidone, water, or acetone.

[0011] In an optional embodiment, the fluorinated spherical particles are modified by grafting a fluorinated monomer onto the surface of the spherical particles. The fluorinated monomer is selected from at least one of tridecafluorooctyltriethoxysilane, trifluoropropyltrimethoxysilane, vinylidene fluoride, and trifluorochloroethylene.

[0012] Secondly, the present invention provides a method for preparing the aforementioned current collector, comprising the following steps: The adhesive and solvent are first mixed to obtain the adhesive solution; A conductive material is added to the adhesive solution, and a second mixing treatment is performed to obtain a conductive slurry; Spherical particles are added to the conductive slurry, and a third mixing treatment is performed to obtain a functional coating slurry. The functional coating slurry is applied to the surface of the current collector and then dried to obtain the primer current collector.

[0013] In an optional embodiment, the solid content of the functional coating slurry is 20%-35%, and the viscosity is 1500mPa·s-3500mPa·s; And / or, the dry weight of the coating is 0.5 g / m². 2 -2 g / m 2 The coating speed is 40 m / min-100 m / min.

[0014] In an optional embodiment, the second mixing process includes: after the conductive material is added to the adhesive, high-speed dispersion and sand milling are performed sequentially; And / or, the third mixing process is carried out in a staged addition manner: first, the second spherical particles are added and dispersed under low-speed stirring for 10-15 minutes; then, the first spherical particles are added and dispersed for another 10-15 minutes; and then ultrasonic treatment is performed. And / or, the coating is applied using gravure coating or slot coating; And / or, the drying process is segmented drying.

[0015] In an optional embodiment, the stirring speed of the first mixing process is 300 rpm to 600 rpm, and the stirring time is 60 min to 90 min. And / or, in the second mixing process, the high-speed dispersion speed is 1500rpm-2500rpm, and the dispersion time is 30min-90min; And / or, the medium for the sand milling process is zirconia beads, the particle size of the zirconia beads is 0.05mm-0.2mm, and the sand milling time is 1h-4h; And / or, the speed of the low-speed stirring is 120 rpm to 300 rpm; And / or, the ultrasonic treatment power is 40W-50W, and the time is 20min-30min; And / or, the segmented drying includes pre-drying at a temperature of 75°C-85°C; film formation at a temperature of 105°C-115°C; and curing at a temperature of 120°C-130°C.

[0016] Thirdly, the present invention provides an electrode sheet comprising the base-coated current collector as described in any of the foregoing embodiments, or the base-coated current collector obtained by the preparation method described in any of the foregoing embodiments.

[0017] Fourthly, the present invention provides an electrochemical device that employs the electrode as described in the foregoing embodiments.

[0018] The present invention has the following beneficial effects: This invention pioneers a coating design that synergistically integrates spherical particle anchors and a conductive system, overcoming the deficiency of insufficient interfacial adhesion between the current collector's metal surface and the active material layer. By introducing spherical particles of two different particle sizes and combining them with a specific conductive material, a functional coating with a uniformly distributed multi-level concave-convex anchor structure is constructed on the current collector surface. This effectively enhances the interfacial bonding strength between the binder system of the subsequently coated active material layer and the functional coating, thereby significantly improving the interfacial peel strength between the active material layer and the current collector. Simultaneously, this invention employs carbon nanotubes to create long-range overlaps between the concave-convex anchors, forming continuous conductive bridges. This structure, through interpenetration and overlap, forms continuous conductive pathways within the coating, effectively improving the interfacial contact impedance between the current collector and the active layer. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0020] Addressing the technical problem of weak interfacial bonding due to the scarcity of effective anchoring points between the current collector metal surface and the bonding system, this application proposes a method to precisely construct a multi-level, uniformly distributed uneven anchoring point structure on the coating surface by simultaneously adding spherical particles of two different particle sizes. Furthermore, by selecting specific conductive materials, a continuous conductive network is built between the irregularly shaped particles, ensuring excellent conductivity of the coating. The inventors have constructed an effective anchoring system on the current collector surface, allowing the binder components in the subsequently applied active slurry to fully penetrate, encapsulate, and interlock with these anchoring points, ultimately forming a robust mechanical interlocking structure. This fundamentally and significantly improves the overall bonding strength, rolling resistance, and long-term cycle stability of the electrode.

[0021] In a first aspect, the present invention provides a primer current collector, the primer current collector comprising a current collector and a functional coating disposed on at least one surface of the current collector; the functional coating comprising spherical particles, conductive material and binder in a mass ratio of 1:(0.5-4):(1-6), for example, 1:0.5:1, 1:1:2, 1:2:3, 1:3:4, 1:4:5, etc.; The conductive material includes carbon nanotubes; in the spherical particles, the ratio of the particle size D501 of the first spherical particle to the particle size D502 of the second spherical particle is 1:(1.5-4), for example, it can be 1:1.5, 1:2.0, 1:2.5, 1:3.0, 1:3.5 or 1:4.0, etc.; the spherical particles at least partially protrude from the surface of the functional coating to form an uneven structure; and the carbon nanotubes bridge the spherical particles to form a continuous electron transport pathway.

[0022] The conductive material further includes carbon black, preferably with a mass ratio of carbon black to carbon nanotubes of 1:(2-25), such as 1:2, 1:5, 1:10, 1:15, 1:20, or 1:25. This application uses a composite of carbon black and carbon nanotubes. The carbon black fills the underlying pores, forming a dense and highly conductive system; the carbon nanotubes are interspersed within, building a long-range conductive framework. Through their synergy, a conductive network structure with both high conductivity and structural stability is constructed, which not only improves the adhesion and conductivity of the coating itself but also provides support for subsequent structures.

[0023] This application also innovatively introduces two types of spherical particles with different particle sizes, which are uniformly embedded inside the aforementioned conductive network structure and at least partially protrude from the coating surface to form stable and uniformly distributed micron-sized protrusions. These protrusions become key anchor points. During the subsequent coating process of the active material slurry, the binder can wet and encapsulate these protrusions of the spherical particles. After the slurry dries and cures, the binder can not only bond through intermolecular forces (van der Waals forces), but more importantly, it forms a stable mechanical interlocking structure with the spherical particle anchor points. This dual-binding mechanism can effectively solve the problems of easy delamination and powder shedding at smooth interfaces.

[0024] In some preferred embodiments, the spherical particles may be selected from at least one of inorganic spherical particles (such as silica, alumina) or polymeric spherical particles (such as polymethyl methacrylate).

[0025] Furthermore, compared to using spherical particles of a single size, combining large-diameter second spherical particles with small-diameter first spherical particles enables the construction of a multi-level anchor structure on the coating surface. The large-diameter second spherical particles form prominent, higher "primary anchors," providing strong mechanical interlocking; the small-diameter first spherical particles form relatively lower "secondary anchors," filling the gaps between the primary anchors and effectively increasing the anchor density per unit area. This synergistic effect results in a more diverse anchor structure on the coating surface in terms of scale and a denser spatial distribution, thereby further enhancing the interfacial bonding strength.

[0026] Preferably, the mass ratio of the first spherical particle to the second spherical particle is 1:(0.5-2), for example, it can be 1:0.5, 1:1.0, 1:1.5, or 1:2.0, etc. If the content of large-diameter second spherical particles is too high (the mass ratio of the first spherical particle to the second spherical particle is less than 1:2), there will be insufficient anchor points and inadequate gap filling; if the content of small-diameter first spherical particles is too high (the mass ratio of the first spherical particle to the second spherical particle is greater than 1:0.5), there will be a lack of strong main anchor points, resulting in insufficient peel strength.

[0027] Preferably, the particle size D501 of the first spherical particle is 0.5μm-1μm, for example, it can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm, etc.; the particle size D502 of the second spherical particle is 1.5μm-2.0μm, for example, it can be 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm or 2.0μm, etc.; the sphericity is not less than 95%, for example, it can be 95%, 96%, 97%, 98% or 99%, etc.; and the uniformly dispersed spherical particles also play a role similar to a "microskeleton" inside the coating, which can suppress the generation and propagation of interfacial microcracks caused by repeated volume expansion and contraction stress during the charging and discharging process of the active material to a certain extent, which helps to improve the long-cycle stability of the battery.

[0028] In this structure, the large-diameter second spherical particles effectively form the framework, while the small-diameter first spherical particles fully fill the gaps between the large-diameter second spherical particles, creating a multi-level anchor point structure with varying heights and uniform distribution. The anchor point density and interfacial bonding strength are both at optimal levels. If the sizes of the two types of spherical particles are too close (the ratio of particle size D501 to particle size D502 is greater than 1:1.5), it is difficult to form an effective framework-filling structure. If the small-diameter first spherical particles are too small relative to the large-diameter second spherical particles (the ratio of particle size D501 to particle size D502 is less than 1:4), they cannot effectively fill the gaps between the large-diameter second spherical particles.

[0029] Furthermore, the multi-level anchor point structure exhibits superior morphology retention during roll forming. The large-diameter second spherical particles, acting as the primary load-bearing points, can concentrate and disperse interfacial stress over a larger area; the small-diameter first spherical particles, acting as secondary load-bearing points, further refine the stress distribution and suppress the initiation of microcracks. Even after high-pressure compaction roll forming, the coating surface still retains a large number of effective interlocking sites.

[0030] Especially when preparing high-density high-pressure compaction electrodes, the anchor points formed by single-size spherical particles are easily flattened by roller pressing. However, by using spherical particles of two mixed sizes, it is possible to form staggered and uneven anchor points, and a large number of interlocking sites can still be retained after roller pressing.

[0031] In some preferred embodiments of this application, the particle size D503 of the carbon black is 20nm-40nm, and can be 20nm, 25nm, 30nm, 35nm or 40nm, etc.; its main function is to fully fill the micro gaps of the coating, thereby ensuring a conductive network with high conductivity and high density.

[0032] In some preferred embodiments, the diameter of the carbon nanotubes is 10 nm-20 nm, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm. In the system, the carbon nanotubes are mainly used to intersect and fix the spherical particles, preventing the spherical particles from agglomerating and settling during coating and drying. The anchor points formed by the spherical particles are not randomly distributed, but are an ordered structure fixed by the carbon nanotube network. Specifically, the carbon nanotubes intersect between adjacent spherical particles and fix them, thereby forming a uniformly distributed array of anchor points in the functional coating.

[0033] Therefore, the preferred carbon nanotube length L in this application satisfies the relationship between the particle size D501 of the first spherical particle and the particle size D502 of the second spherical particle: 2D501≤L≤6D502. This allows the carbon nanotube to effectively bridge the protrusions of adjacent spherical particles, building a continuous conductive bridge between the concave and convex anchor points. This avoids breakage of the conductive network at the anchor point protrusions, forming a synergistic reinforcement of concave and convex anchor points and conductive network. Through interpenetration and overlapping, it forms a continuous conductive path in the coating, effectively improving the interfacial contact impedance between the current collector and the active layer. Randomly proportioned carbon nanotubes L cannot effectively bridge the spherical particles, resulting in a limited decrease in interfacial impedance.

[0034] In some preferred embodiments, the current collector is selected from at least one of aluminum foil, copper foil, composite aluminum foil, and composite copper foil; and the thickness of the functional coating is 0.8μm-2μm, for example, it can be 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, or 2μm, etc.

[0035] Furthermore, in order to further optimize the dispersion uniformity of spherical particles in functional coatings and their interfacial bonding performance with commonly used binder systems, as a preferred embodiment of the present invention, the spherical particles may be subjected to fluorination modification treatment, wherein the fluorination modification is to graft fluorine-containing groups or fluorine-containing segments onto the surface of the spherical particles by chemical bonding.

[0036] Further research by the inventors revealed that fluorination modification of spherical particles reduces surface polarity and surface energy. This change generally improves the interfacial compatibility between spherical particles and various organic binder systems, facilitating the establishment of a tighter and more stable interfacial contact between the spherical particles and the binder. Simultaneously, fluorination modification effectively weakens the polar interactions on the surface of the spherical particles, significantly inhibiting hydrogen-bonded aggregation in the slurry system. This improves the dispersion uniformity and anchor point distribution consistency of the spherical particles in the coating, further optimizing the surface roughness uniformity and long-term service stability of the coating. Especially when the binder is a PVDF system, the fluorinated spherical particle surface and PVDF molecular chains exhibit a superior interfacial affinity due to the "like dissolves like" principle, further suppressing long-term creep slippage of PVDF at the anchor points, resulting in a particularly significant improvement in interfacial bonding stability.

[0037] It is understood that in the basic technical solution of this invention, unmodified spherical particles, by virtue of their own geometric morphology and particle size advantages, can construct an effective microscopic uneven anchor structure on the coating surface, thereby significantly improving the interfacial bonding strength. Fluorination modification is a further optimization scheme based on this for applications requiring higher durability. Its beneficial effects are evident in different binder systems, and it is particularly suitable for PVDF bonding systems.

[0038] Furthermore, the fluorinated spherical particles are modified by grafting fluorinated monomers onto the surface of the spherical particles, wherein the fluorinated monomers are selected from at least one of tridecafluorooctyltriethoxysilane, trifluoropropyltrimethoxysilane, vinylidene fluoride, or trifluorochloroethylene. Furthermore, the fluorination modification step of the inorganic spherical particles such as alumina or silica includes: Grafting solution preparation: 85 parts anhydrous ethanol + 12 parts deionized water + 0.5 parts glacial acetic acid, stir evenly, slowly add 2.5 parts fluorinated silane, stir at room temperature for 30 minutes to complete silane hydrolysis, and generate fluorinated silanol intermediate; Pretreatment of spherical particle dispersion: Inorganic spherical particles are added to hydrolysate, with solid content controlled at 20 wt%, stirred at low speed for 30 min, and ultrasonically dispersed for 10 min to break up the spherical particle agglomerates; Grafting reaction: The system is heated to 60-70℃ and stirred under constant temperature for 2 hours. The silanol and the hydroxyl groups on the surface of the spherical particles undergo dehydration condensation, and fluorinated alkyl segments are covalently grafted. Post-processing (including cleaning, purification, drying and curing): The spherical particles were separated by centrifugation, washed three times with anhydrous ethanol to remove unreacted free silane, and then vacuum dried at 80°C for 12 hours to obtain fluorine-modified inorganic spherical particles with fluorinated alkyl chains grafted onto their surface.

[0039] The surface of the fluorine-modified inorganic spherical particles is a nanoscale fluorine-containing molecular layer: the Si-O-Si covalent bonds inside the fluorine-containing molecular layer are firmly anchored to the surface of the spherical particles, and a large number of -CF3 and -CF2 fluoroalkyl groups are exposed on the surface.

[0040] Furthermore, the fluorination modification of organic polymer spherical particles such as polymethyl methacrylate is achieved through PVDF compatible segment grafting modification, including the following steps: PMMA spherical particles were ultrasonically dispersed in acetone and heated to 75°C. Vinylidene fluoride monomer (VDF) and / or chlorotrifluoroethylene monomer (CTFE) were introduced, and benzoyl peroxide initiator (BPO) was added. The suspension polymerization reaction was carried out for 4 hours. Short PVDF branches were grafted onto the surface of the PMMA spherical particles to form a core-shell structure (PMMA core + PVDF shell). The particles were then filtered, washed with acetone, and vacuum dried to obtain modified PMMA spherical particles.

[0041] The modified PMMA spherical particle shell is composed of PVDF homologous segments, allowing the PVDF binder in the subsequent active material to directly entangle with the shell molecules, thus significantly improving the interfacial bonding force.

[0042] It is easy to understand that the spherical particles selected in this application do not participate in the conductive process. Their chemical structure is stable and can play a key physical support role in the thick active coating system. This support role can not only buffer the expansion stress caused by the volume change of the active material during the charge and discharge cycle of the battery, but also effectively suppress the interface debonding phenomenon and the generation of microcracks, thereby enhancing the overall stability of the electrode structure.

[0043] In some preferred embodiments, the raw materials for preparing the functional coating, by 100% by mass, include: 4%-8% binder, 2%-6% conductive material, 1.5%-4.0% spherical particles, and the balance being solvent; The adhesive can be selected from at least one of polyvinylidene fluoride (PVDF), polyacrylic resin, or styrene-butadiene rubber (SBR).

[0044] In some preferred embodiments, the solvent includes, but is not limited to, at least one of N-methylpyrrolidone (NMP), water, or acetone.

[0045] This application constructs a specific microstructure in the functional coating. This design can form a large number of uniformly distributed micro-anchor points on the coating surface, allowing the PVDF binder in the subsequent active material slurry to fully wet, completely cover, and firmly engage these anchor points. This significantly enhances the interfacial mechanical anchoring effect at the physical level and effectively improves the bonding force between the active layer and the current collector.

[0046] Secondly, the present invention provides a method for preparing a primer current collector as described in any of the foregoing embodiments, comprising the following steps: S1. The adhesive and solvent are first mixed to obtain an adhesive solution; In some preferred embodiments, the stirring speed for the first mixing process is 300 rpm to 600 rpm, for example, 300 rpm, 400 rpm, 500 rpm or 600 rpm, and the stirring time is 60 min to 90 min, for example, 60 min, 70 min, 80 min or 90 min; S2. Add conductive material to the adhesive solution and perform a second mixing process to obtain a conductive slurry; Specifically, the second mixing process includes: after the conductive material is added to the adhesive, high-speed dispersion and sand milling processes are performed sequentially; In some embodiments of this application, the high-speed dispersion rotation speed of the second mixing process is 1500rpm-2500rpm, for example, it can be 1500rpm, 1700rpm, 1900rpm, 2100rpm, 2300rpm or 2500rpm, etc., and the dispersion time is 30min-90min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, etc. The grinding medium is zirconia beads with a particle size of 0.05 mm to 0.2 mm, such as 0.05 mm, 0.10 mm, 0.15 mm or 0.20 mm, etc. The grinding time is 1 h to 4 h, such as 1 h, 2 h, 3 h or 4 h.

[0047] S3. Add spherical particles to the conductive paste, and after a third mixing treatment, obtain a functional coating paste; In some preferred embodiments, the solid content of the functional coating slurry is 20%-35%, for example, it can be 20%, 25%, 30% or 35%; the viscosity is 1500 mPa·s-3500 mPa·s, for example, it can be 1500 mPa·s, 2000 mPa·s, 2500 mPa·s, 3000 mPa·s or 3500 mPa·s.

[0048] During the slurry preparation process, the third mixing treatment adopts a staged addition method: first, add the second spherical particles and disperse them under low-speed stirring for 10-15 minutes; then add the first spherical particles and continue to disperse them for 10-15 minutes; then perform ultrasonic treatment. In some preferred embodiments, the low-speed stirring speed is 120 rpm to 300 rpm, for example, 120 rpm, 180 rpm, 240 rpm or 300 rpm, and the stirring time is 20 min to 30 min, for example, 20 min, 25 min or 30 min; The power of ultrasound-assisted dispersion is 40W-50W, for example, 40W, 42W, 44W, 46W, 48W or 50W, and the time is 20min-30min, for example, 20min, 22min, 24min, 26min, 28min or 30min.

[0049] S4. The functional coating slurry is applied to the surface of the current collector and dried to obtain the primer current collector.

[0050] In some preferred embodiments, the dry weight of the coating is 0.5 g / m². 2 -2 g / m 2 For example, it can be 0.5 g / m 2 1g / m 2 1.5 g / m 2 Or 2 g / m 2 The coating speed is 40 m / min-100 m / min, for example, it can be 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min, 90 m / min or 100 m / min, etc.

[0051] In some preferred embodiments, the segmented drying process includes: a pre-drying temperature of 75℃-85℃ and a pre-drying time of 1min-3min; a film-forming drying temperature of 105℃-115℃ and a film-forming drying time of 2min-5min; and a complete curing temperature of 120℃-130℃ and a complete curing time of 3min-8min.

[0052] In some embodiments of this application, the coating is applied using gravure coating or slot coating.

[0053] Thirdly, the present invention provides an electrode sheet comprising the base-coated current collector as described in any of the foregoing embodiments, or the base-coated current collector obtained by the preparation method described in any of the foregoing embodiments.

[0054] Fourthly, the present invention provides an electrochemical device that employs the electrode as described in the foregoing embodiments.

[0055] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0056] Example 1 This embodiment provides a base coating current collector, including a functional coating disposed on a composite aluminum foil: 1. Preparation of raw materials for functional coating: The raw materials for preparing the functional coating include, by 100% by mass: 6% PVDF binder, 4% conductive material, 3% spherical particles, and the balance being N-methylpyrrolidone; wherein, the mass ratio of carbon black to carbon nanotubes in the conductive material is 1:15; the mass ratio of the first spherical particle to the second spherical particle is 1:1; the particle size D501 of the first spherical particle is 0.5μm, and the particle size D502 of the second spherical particle is 2μm; the diameter of the carbon nanotube is 15nm, and the length L is 4μm; the spherical particles are alumina with a sphericity of 95%.

[0057] 2. Preparation of functional coating slurry: (1) Add PVDF adhesive to N-methylpyrrolidone and stir at 450 rpm for 75 min to fully mix and obtain adhesive solution; (2) Carbon black and carbon nanotubes were added to the adhesive solution in sequence, and high-speed dispersion (dispersion at 2000 rpm for 60 min) and sand milling (sanding with 0.1 mm zirconium oxide for 2 h) were carried out in sequence to obtain a uniformly dispersed conductive paste. (3) Add the second spherical particles to the conductive slurry, stir at 200 rpm for 10 min, then add the first spherical particles, stir at 200 rpm for 15 min; finally, sonicate at 45 W for 25 min and mix thoroughly to obtain the functional coating slurry; the solid content of the functional coating slurry is 27% and the viscosity is 2500 mPa·s. (4) The functional coating slurry is uniformly coated onto the surface of the composite aluminum foil by micro-gravure coating and then subjected to segmented drying treatment: firstly, it is pre-dried at 80°C, then the coating is formed at 110°C, and finally it is completely cured at 125°C to obtain a coated current collector with a functional coating. The dry weight of the coating is 1.2 g / m². 2 The coating speed is 70 m / min, and the thickness of the functional coating is 1.4 μm.

[0058] Example 2 This embodiment provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that: the raw materials for preparing the functional coating, by 100% by mass, include 4% PVDF binder, 2% conductive material, 1.5% spherical particles, and the balance being N-methylpyrrolidone; the solid content of the functional coating slurry is 20%, and the viscosity is 1500 mPa·s.

[0059] Example 3 This embodiment provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that: the raw materials for preparing the functional coating, by 100% by mass, include 8% PVDF binder, 6% conductive material, 4% spherical particles, and the balance being N-methylpyrrolidone; the solid content of the functional coating slurry is 35%, and the viscosity is 3500 mPa·s.

[0060] Example 4 This embodiment provides a primer current collector, whose raw materials and steps are the same as those in Embodiment 1, except that: the mass ratio of carbon black to carbon nanotubes in the conductive material is 1:2; the mass ratio of the first spherical particle to the second spherical particle in the spherical particles is 1:0.5; the particle size D501 of the first spherical particle is 1 μm, and the particle size D502 of the second spherical particle is 1.5 μm.

[0061] Example 5 This embodiment provides a primer current collector, whose raw materials and steps are the same as those in Embodiment 1, except that: the mass ratio of carbon black to carbon nanotubes in the conductive material is 1:25; the mass ratio of the first spherical particle to the second spherical particle in the spherical particles is 1:2; the particle size D501 of the first spherical particle is 0.5 μm, and the particle size D502 of the second spherical particle is 2.0 μm.

[0062] Example 6 This embodiment provides a primer current collector, whose raw materials and steps are the same as in Example 1, the only difference being that the dry weight of the coating is 0.5 g / m³. 2 The coating speed is 100 m / min, and the thickness of the functional coating is 0.8 μm.

[0063] Example 7 This embodiment provides a primer current collector, whose raw materials and steps are the same as in Example 1, the only difference being that the dry weight of the coating is 2 g / m³. 2 The coating speed is 40 m / min, and the thickness of the functional coating is 2 μm.

[0064] Example 8 This embodiment provides a primer current collector, whose raw materials and steps are the same as those in Example 1, the only difference being that the spherical particles are fluorine-modified spherical particles modified by grafting tridecafluorooctyltriethoxysilane onto the surface of alumina.

[0065] Comparative Example 1 This comparative example provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that the conductive material is carbon black.

[0066] Comparative Example 2 This comparative example provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that the particle size of the spherical particles is 0.5 μm.

[0067] Comparative Example 3 This comparative example provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that the particle size of the spherical particles is 2.0 μm.

[0068] Comparative Example 4 This comparative example provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that the length L of the carbon nanotube is 0.5 μm.

[0069] Comparative Example 5 This comparative example provides a primer current collector, whose raw materials and steps are the same as those in Example 1, except that the length L of the carbon nanotube is 15 μm.

[0070] Experimental Example 1 The performance of the primer current collectors prepared in Examples 1-8 and Comparative Examples 1-5 was tested, and the results are shown in Table 1.

[0071] Electrode interface peel strength (used to evaluate the mechanical anchoring effect of the coating): NCM811 positive electrode slurry (area density 220 g / m²) was coated on one side of the primer aluminum foil in each example / comparative example. 2 Compacted density 4.3 g / cm³ 3 Dry at 120℃, roll to the target compaction degree, and cut 15mm×100mm standard electrode sheets; use a universal tensile testing machine to fix one end of the electrode sheet, peel off the active material layer at a peel angle of 180° and a tensile speed of 50mm / min, and record the average peel force in the stable stage; peel strength = average peel force / sample width, unit N / m, and 5 parallel samples are tested for each group of samples and the average value is taken; the higher the value, the stronger the bonding force between the current collector and the active layer interface, and the less likely it is to fall off or delaminate during rolling and cycling.

[0072] Electrode interface impedance (evaluating the conductivity of the three-dimensional conductive network): Using the same standard positive electrode as above, cut Φ16mm circular electrodes and assemble CR2032 button half-cells with lithium metal sheets and 1M LiPF6 electrolyte; testing equipment: electrochemical workstation; allow the battery to stand for 12 hours until the voltage stabilizes, then apply a small 10mV AC signal with a frequency range of 10... 6 Hz~0.01Hz, EIS was fitted to extract the high-frequency interfacial charge transfer impedance Rct; three batteries were tested in parallel in each group and the average value was taken; the lower the impedance value, the better the continuity of the conductive path of the coating, the smaller the battery polarization and the better the fast charging performance.

[0073] Table 1. Performance Test Results

[0074] As shown in Table 1, the embodiments of this application use spherical particles of two different sizes to construct a multi-level anchor point structure on the coating surface, demonstrating that the staggered uneven structure can form effective mechanical interlocking and significantly improve interfacial adhesion. Furthermore, Example 8 uses fluorinated modified spherical particles, verifying that fluorinated modified spherical particles have a better compatibility with PVDF binder. In the embodiments of this application, carbon nanotubes are used to bridge spherical particles to build long-range conductive pathways, resulting in a significant decrease in impedance. In Comparative Examples 4 and 5, the impedance significantly increases when the carbon nanotube length L deviates from the 2D501-6D502 range, verifying the crucial role of carbon nanotube length matching particle size.

[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A primer current collector, characterized in that, The primer current collector includes a current collector and a functional coating disposed on at least one surface of the current collector; the functional coating includes spherical particles, conductive material and binder in a mass ratio of 1:(0.5-4):(1-6); The conductive material includes carbon nanotubes; in the spherical particles, the ratio of the particle size D501 of the first spherical particle to the particle size D502 of the second spherical particle is 1:(1.5-4); the spherical particles at least partially protrude from the surface of the functional coating to form an uneven structure, and the carbon nanotubes bridge the spherical particles to form a continuous electron transport pathway.

2. The primer current collector according to claim 1, characterized in that, The conductive material also includes carbon black, and the mass ratio of carbon black to carbon nanotubes is 1:(2-25). And / or, the mass ratio of the first spherical particle to the second spherical particle is 1:(0.5-2); And / or, the length L of the carbon nanotube satisfies the following relationship with the particle size D501 of the first spherical particle and the particle size D502 of the second spherical particle: 2D501≤L≤6D502; And / or, the particle size D503 of the carbon black is 20nm-40nm.

3. The primer current collector according to claim 1, characterized in that, The diameter of the carbon nanotubes is 10nm-20nm; And / or, the spherical particles comprise at least one of silica, alumina, or polymethyl methacrylate polymer; And / or, the sphericity of the spherical particles is not less than 95%; And / or, the adhesive is at least one of polyvinylidene fluoride, polyacrylic acid resin or styrene-butadiene rubber; And / or, the current collector is selected from at least one of aluminum foil, copper foil, composite aluminum foil, and composite copper foil.

4. The primer current collector according to claim 1, characterized in that, The particle size D501 of the first spherical particle is 0.5μm-1μm, and the particle size D502 of the second spherical particle is 1.5μm-2.0μm; And / or, the thickness of the functional coating is 0.8μm-2μm; And / or, the spherical particles are fluorine-modified spherical particles.

5. The primer current collector according to claim 1, characterized in that, The raw materials for preparing the functional coating, by 100% by mass, include: 4%-8% binder, 2%-6% conductive material, 1.5%-4.0% spherical particles, and the balance being solvent; The solvent is selected from at least one of N-methylpyrrolidone, water, or acetone.

6. The primer current collector according to claim 4, characterized in that, The fluorinated spherical particles are modified by grafting fluorinated monomers onto the surface of the spherical particles. The fluorinated monomers are selected from at least one of tridecafluorooctyltriethoxysilane, trifluoropropyltrimethoxysilane, vinylidene fluoride, and trifluorochloroethylene.

7. A method for preparing a primer current collector as described in any one of claims 1-6, characterized in that, Includes the following steps: The adhesive and solvent are first mixed to obtain the adhesive solution; A conductive material is added to the adhesive solution, and a second mixing treatment is performed to obtain a conductive slurry; Spherical particles are added to the conductive slurry, and a third mixing treatment is performed to obtain a functional coating slurry. The functional coating slurry is applied to the surface of the current collector and then dried to obtain the primer current collector.

8. The preparation method according to claim 7, characterized in that, The solid content of the functional coating slurry is 20%-35%, and the viscosity is 1500 mPa·s-3500 mPa·s; And / or, the dry weight of the coating is 0.5 g / m². 2 -2 g / m 2 The coating speed is 40 m / min-100 m / min.

9. The preparation method according to claim 7, characterized in that, The second mixing process includes: after the conductive material is added to the adhesive, high-speed dispersion and sand milling are performed sequentially; And / or, the third mixing process is carried out in a staged addition manner: first, the second spherical particles are added and dispersed under low-speed stirring for 10-15 minutes; then, the first spherical particles are added and dispersed for another 10-15 minutes; and then ultrasonic treatment is performed. And / or, the coating is applied using gravure coating or slot coating; And / or, the drying process is segmented drying.

10. The preparation method according to claim 9, characterized in that, The stirring speed for the first mixing process is 300 rpm to 600 rpm, and the stirring time is 60 min to 90 min. And / or, in the second mixing process, the high-speed dispersion speed is 1500rpm-2500rpm, and the dispersion time is 30min-90min; And / or, the medium for the sand milling process is zirconia beads, the particle size of the zirconia beads is 0.05mm-0.2mm, and the sand milling time is 1h-4h; And / or, the speed of the low-speed stirring is 120 rpm to 300 rpm; And / or, the ultrasonic treatment power is 40W-50W, and the time is 20min-30min; And / or, the segmented drying includes pre-drying at a temperature of 75°C-85°C; film formation at a temperature of 105°C-115°C; and curing at a temperature of 120°C-130°C.

11. An electrode sheet, characterized in that, The electrode comprises the undercoated current collector as described in any one of claims 1 to 6 or the undercoated current collector prepared by the preparation method described in any one of claims 7 to 10.

12. An electrochemical device, characterized in that, The electrochemical device includes the electrode as described in claim 11.